Resilient and Resourceful? A Case Study on How the Poor Cope in Kerala, India - Bejoy K. Thomas, Roldan Muradian, Gerard de Groot and Arie de Ruijter
In the backdrop of the popularisation of social capital, it has become fashionable indevelopment circles to highlight the resilience of the poor in the midst of stresses andshocks as well as their resourcefulness. Expressing scepticism, this article argues thatsocial capital is a `conditional' resource for the poor, availability of which is dependanton the presence of a `critical mass' of other resources. The State plays a pivotal role increating this `critical mass'. Household level case studies from a village in Kerala, India, on how the poor cope with vulnerable situations, are used to illustrate this point